2018
DOI: 10.1590/0074-02760170307
|View full text |Cite
|
Sign up to set email alerts
|

Making the invisible visible: searching for human T-cell lymphotropic virus types 1 and 2 (HTLV-1 and HTLV-2) in Brazilian patients with viral hepatitis B and C

Abstract: With this study, the authors hope to alert clinicians regarding the presence of human T-cell lymphotropic virus type 1 and 2 (HTLV-1/-2) infections in patients with viral hepatitis B and C in Brazil. HTLV-1/-2 were detected in 1.3% of hepatitis B virus (HBV)- and 5.3% of hepatitis C virus (HCV)-infected blood samples sent for laboratory viral load measurements. A partial association of human immunodeficiency virus (HIV)-1 and HTLV-1/-2 infection was detected in patients with HCV (HIV+, 27.3%), whereas this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
3
24
1
Order By: Relevance
“…Our study is similar to studies conducted in Japan, in which the prevalence of HTLV / HCV coinfection was estimated in HTLV endemic areas [12,15] and in donor donors blood from Ribeirão Preto [22]. In contrast to our analysis, previous studies have evaluated HTLV infection in individuals with hepatitis C who received treatment [20,21]. We found that HTLV-positive individuals presented a significantly higher prevalence for anti-HCV and also had a higher probability of acquiring hepatitis C (OR: 22.9) compared to HTLV-negative individuals.…”
Section: Plos Onesupporting
confidence: 87%
See 2 more Smart Citations
“…Our study is similar to studies conducted in Japan, in which the prevalence of HTLV / HCV coinfection was estimated in HTLV endemic areas [12,15] and in donor donors blood from Ribeirão Preto [22]. In contrast to our analysis, previous studies have evaluated HTLV infection in individuals with hepatitis C who received treatment [20,21]. We found that HTLV-positive individuals presented a significantly higher prevalence for anti-HCV and also had a higher probability of acquiring hepatitis C (OR: 22.9) compared to HTLV-negative individuals.…”
Section: Plos Onesupporting
confidence: 87%
“…In Brazil, epidemiological data on the rate of HTLV/HCV coinfection remains scarce. Only three studies that estimated the prevalence of HTLV/HCV coinfection were recovered in the scientific literature: one in the city of São Paulo and one in the city of Rio de Janeiro, both studies evaluated the coinfection of HTLV / HCV in individuals undergoing HCV treatment [20,21]. The third study was performed in the city of Ribeirão Preto (São Paulo) and evaluated for 11 years the seroprevalence of HTLV and co-infections with other sexually transmitted diseases such as HIV, syphilis and HBV [22].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The LIA confirmed the presence of HTLV-2 in 11/21 (52.4%) of the WB-indeterminate samples. The high number of HTLV-2-positive samples in G2 leads us to suppose that these patients acquired HBV and HCV, as well HTLV-1/2 and HIV, at the same time, probably by the parenteral route and prior to the time when serological testing for HIV and HBV (1989), and subsequently for HTLV and HCV (1993), became mandatory in blood banks throughout Brazil; in addition, intravenous drug addiction was more frequent in this country, as previously described (18)(19)(20). Corroborating this hypothesis, older age and male sex predominated in G2.…”
Section: Discussionmentioning
confidence: 55%
“…The serum samples employed in the present study were obtained from the biorepositories of the HTLV Research Laboratory (LPHTLV), Department of Immunology, Adolfo Lutz Institute (IAL), located in São Paulo, Brazil, and the Integrated and Multidisciplinary HTLV Center (CHTLV), located at the Bahiana School of Medicine and Public Health (EBMSP) in Salvador, Bahia, Brazil. Briefly, the samples from São Paulo were collected between 2012 and 2016 in the course of previous studies designed to detect the prevalence of HTLV-1/2 in HIV-infected individuals as well as in patients with hepatitis B virus (HBV) or hepatitis C virus (HCV) infection in the state of São Paulo, Brazil (14,15,(18)(19)(20). The samples from Salvador, Bahia, were obtained by routine diagnostic procedures at an outpatient clinic in Salvador (CHTLV) from 2015 to 2017; these samples were additionally used to assess the performances of four commercially available HTLV serological screening tests in Brazil (21).…”
Section: Methodsmentioning
confidence: 99%